Fatigue have impact on the sexual problems in Chinese females with systemic lupus erythematosus - Lijuan Zhang; Beiwen Wu; Junna Ye (BMC Women's Health, 2022)
Abstract Background Systemic lupus erythematosus (SLE) might affect all aspects of life including sexual function; previous study indicated that fatigue was the risk factor of sexual dysfunction. The current study aims to investigate the effects of SLE on Chinese mainland female patients’ sexual problems compared with healthy subjects and to investigate the relationship among fatigue, disease parameters, depression, quality of life and sexual problems in Chinese female patients with SLE. Methods A total of 128 female SLE patients (mean age: 43.65 ± 7.13 years) and 121 healthy female controls (mean age 43.59 ± 6.57 years) were included in this cross-sectional study. All data were collected consecutively by face-to-face questionnaires from January 2021 to December 2021. SLE patients completed questionnaires for demographic or clinical variables, the 10-cm Visual Analog Scale for pain, the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) for disease activity, the multidimensional fatigue inventory (MFI) for fatigue, the patient health questionnaire-9 (PHQ-9) for depression, the Female Sexual Function Index (FSFI) for problems, and the Short Form 12 health survey for quality of life. Independent sample t-test, Mann–Whitney U-test, Chi-square test, and forward stepwise binary logistic regression model were used to analyze these data. Results Our results showed that the prevalence of female sexual problems was 78.9% in SLE patients, which was significantly higher than the controls (56.7%; p < 0.05). The results found that having child (OR 23.04; p < 0.000), age (OR 1.11; p = 0.002), DMARDs usage (OR 0.04; p = 0.004), MFI total score (OR 1.06; p = 0.006), and disease duration (OR 1.16; p = 0.043) were the potential risk factors of female sexual problems by forward stepwise binary logistic regression. Conclusion The present study reported that female sexual problems was more common in Chinese SLE female patients compared to controls. Having child, age, DMARDs usage, fatigue, and disease duration had great impacts on female sexual problems in Chinese SLE patients. Rheumatologists and nurses should pay close attention to SLE female patients’ sexual problems, especially those having no child, older age, not using DMARDs, fatigue, or long disease duration by health education or other methods to improve their sexual problems, and ultimately improve SLE patients’ quality of life.